Embryo growth and seed germination requirements in underdeveloped embryos of Elwendia caroides and E. wolfii (Apiaceae) - Rahimi, Hero; Rezanejad, Farkhondeh; Ayatollahi, Seyed Abdulmajid; Sharifi-Sirchi, Gholam Reza; Rahimi, Himan (Mediterranean Botany, 2024)
Elwendia wolfii and E. caroides are two herbaceous perennials that were initially classified in the Bunium genus and later transferred to the Elwendia genus. They are a rich source of bioactive and antioxidant compounds and have the potential to become sources of oil-bearing crops. The aim of this study was to investigate requirements for embryo growth, dormancy break and seed germination in these two species. The effects of gibberellic acid (GA3) and dry storage were also examined to determine the type of dormancy. The pericarps and seed coats of both species were water-permeable, and the embryos were small and differentiated but underdeveloped, with initial embryo lengths of 0.28 mm in E. wolfii and 0.96 mm in E. caroides, respectively. These underdeveloped embryos were either di (>98%) or tricotyledonous (<2%) and required cold temperatures to grow, indicating that these seeds had morphological dormancy (MD). The critical length required for germination was 3.44 mm for E. wolfii and 4.17 mm for E. caroides. However, seeds of both species reached less than 50% final germination if subjected only to cold incubation. Higher final germination was possible if seeds were pre-treated with dry cold storage (-22 ºC) or exposed to GA3, indicating the existence of physiological dormancy (PD) in part of the seed population. Therefore, both species had non-deep complex morphophysiological dormancy (MPD). This study demonstrates that E. caroides and E. wolfii share the same germination requirements, suggesting a common ecological strategy in their seed germination process.